"Nudge" and statistics. Issue 1 (29th January 2020) - Pilling, Mark
Abstract : Mark Pilling highlights the role of statistics and study design in helping policy‐makers and business leaders to determine the effectiveness of behaviour change interventions Abstract : Mark Pilling highlights the role of statistics and study design in helping policy‐makers and business leaders to determine the effectiveness of behaviour change interventions.